A new hybrid and optimized algorithm for drivers’ drowsiness detection - Mouad Elmouzoun Elidrissi; Elmaati Essoukaki; Lhoucine Ben Taleb; Azeddine Mouhsen; Mohammed Harmouchi (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
When the roads are monotonous, especially on the highways, the state of vigilance decreases and the state of drowsiness appears. Drowsiness is defined as the transitional phase from the awake to the sleepy state. However, In Morocco, the majority of fatal accidents on the highway are caused by drowsiness at the wheel, reaching 33.33% rate. Therefore, we proposed the conception and realization of an automatic method based on electroencephalogram (EEG) signals that can predict drowsiness in real time. The proposed work is based on time-frequency analysis of EEG signals from a single channel (FP1-Ref), and drowsiness is predicted using a personalized and optimized machine learning model (optimized decision tree classification method) under Python. The results are much significant and optimized, improving the accuracy from 95.7% to 96.4% and a time consuming from 0.065 to 0.053 seconds.